Synthesis, Antioxidant and Antitumor Activity of Some Substituted 9-Anilinoacridine and 4-Anilinoquinolines Derivatives - Agili, Fatimah A. (Current Organic Synthesis, 2018)
Background: Acridine and quinoline derivatives have a wide range of biological activities such as antioxidant and antitumor where quinoline derivatives intercalate between base pairs of double-stranded DNA through π-π interactions. Therefore, the development of new compounds with antitumor activity could be an important therapeutic strategy against this metabolic syndrome. Objective: This study was undertaken to synthesize different series of new anilinoacridines and anlinoquinoline with different substituents having biological activity. Materials and Methods: A series of new anilinoacridines and anlinoquinoline with different substituents was prepared by condensation of methyl 3-amino-4-methoxybenzoate hydrochloride with 9- chloroacridine and 4- chloroquinoline to give the target derivatives. Results: New anilinoacridines and anlinoquinoline with different substituents have been synthesized as antioxidant and anti-cancer agents. The structure of the synthesized compounds was confirmed by using spectral methods (FT-IR, 1H-NMR). The antioxidant activity of the synthesized compounds was evaluated by using DPPH radical scavenging ability. Also, the anti-cancer activity was evaluated using lung carcinoma, breast adenocarcinoma and liver carcinoma. The developed compounds 4a, b, 5a,b, 7a,b and 8a,b have shown a potent antioxidant activity. On the other hand, 4a, b, 5a and 7a exhibited the best antitumor activity against both A-549 and MCF7 cancer cells. Conclusion: For the active developed compounds, the most active antioxidant and antitumor one was 4a which registered the highest radical scavenging as well as antitumor activity.
Keywords: anlinoquinoline